Level of episiotomy practice and its disparity among primiparous and multiparous women in Ethiopia: a systematic review and meta-analysis - Aragaw, Fantu Mamo; Belay, Daniel Gashaneh; Endalew, Mastewal; Asratie, Melaku Hunie; Gashaw, Moges; Tsega, Nuhamin Tesfa (Frontiers in Global Women's Health, 2023)
Background: Episiotomy at the time of vaginal birth is a common lifesaving surgical procedure.In Ethiopia, several studies have been conducted concerning the proportion of episiotomy.However, its prevalence varies across these series of studies. Thus, this systematic review and meta-analysis aimed to estimate the level of episiotomy practice and its disparity among primiparous and multiparous women in Ethiopia.The systematic review was reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guideline. We systematically searched the databases: PubMed/MEDLINE, EMBASE, Google Scholar, and Science Direct for studies conducted in Ethiopia that focus on episiotomy. We included all cross-sectional studies, which were published until October 5 th ,2022. Data were analysed using R Version 4.2.1 software. The pooled estimates with 95% confidence intervals (CI) were presented using forest plots. A random effects meta-analysis was conducted on extracted crude rates to arrive at national and regional pooled estimates for the country. I squared test and Egger's regression test was used to assess heterogeneity and publication bias respectively.Results: Our search yielded 390 articles. Thirteen studies covering five administrative regions and 6404 vaginally delivered women were involved. The mean age of the study participants ranged from 22-27.7 years. The estimated overall pooled prevalence of episiotomy in Ethiopian women was 42.75 % (95% CI: 34.97, 50.54%). In the subgroup analysis, the pooled prevalence of episiotomy was 61.45% (95%CI: 51.11%, 71.80%) among primiparous women, meanwhile, among multiparous women, the pooled estimate appears to be around 30.47% (95% CI: 22.08%, 38.85%).Our findings concluded that the pooled prevalence of episiotomy was higher than the evidence-based WHO recommendations for optimal patient care. Parallel to this, nulliparous women had a higher rate of episiotomy than multiparous women. These findings highlight the importance of continued training for labour ward staff, particularly healthcare providers who often perform majority of deliveries.